2022
DOI: 10.3989/gya.0783211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different extraction methods on saffron antioxidant activity, total phenolic and crocin contents and the protective effect of saffron extract on the oxidative stability of common vegetable oils

Abstract: Saffron consists of bioactive compounds with health-promoting properties and is mainly used in medicine, flavoring and coloring. In this study, we aimed to investigate the effect of extraction methods on the antioxidant activity of saffron (Crocus sativus L.) extracts (SE) and to evaluate the antioxidant performance of SE in vegetable oils. Saffron stigmas were extracted in water, ethanol, methanol, and their combinations using maceration extraction (ME), ultrasonic-assisted extraction (UAE), microwave-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Yalcin et al (2017) reported that the IP of corn oil without and with 2000 ppm of grape seed extract changed from 3.18 to 3.31 -3.41, depending on the seed variety. In another study, saffron extract (1000 ppm) had a similar effect (p < 0.05) with BHT (200 ppm) in preventing the oxidation of vegetable oils (Najafi et al, 2022) The volatile compounds in the flower, leaf, and stem parts of E. Pallida harvested in June, 2009, June, 2010 and August, 2010 are shown in Table 3. Bornyl acetate, caryophyllene E, musk ambrette, germacrene D, α-cubebene, α-copaene, α-humulene, α-muurolol, γ-cadinene, and caryophyllene oxide are some of the major volatile compounds which were identified in all the plant parts of E. pallida.…”
Section: Resultsmentioning
confidence: 76%
“…Yalcin et al (2017) reported that the IP of corn oil without and with 2000 ppm of grape seed extract changed from 3.18 to 3.31 -3.41, depending on the seed variety. In another study, saffron extract (1000 ppm) had a similar effect (p < 0.05) with BHT (200 ppm) in preventing the oxidation of vegetable oils (Najafi et al, 2022) The volatile compounds in the flower, leaf, and stem parts of E. Pallida harvested in June, 2009, June, 2010 and August, 2010 are shown in Table 3. Bornyl acetate, caryophyllene E, musk ambrette, germacrene D, α-cubebene, α-copaene, α-humulene, α-muurolol, γ-cadinene, and caryophyllene oxide are some of the major volatile compounds which were identified in all the plant parts of E. pallida.…”
Section: Resultsmentioning
confidence: 76%
“…The variability in antimicrobial potential recorded by the authors is linked to several direct and indirect factors that accompany the sample from implantation to the final product. These factors include the age of the corms [ 55 ], altitude and climate [ 60 ], drying temperature [ 61 ], storage and packaging [ 62 ], and extraction and analysis methods [ 36 , 63 ]. All these factors can affect the chemical composition of the sample and therefore the results obtained during analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the sensory perception of saffron is closely related The key bioactive compounds are all derived from the carotenoid precursor zeaxanthin through different biosynthetic pathways during the development and drying process of saffron stigmas [26,27]. Briefly, zeaxanthin undergoes oxidative cleavage by the enzyme carotenoid cleavage dioxygenase to form the apocarotenoid crocetin dialdehyde, which is subsequently converted to crocetin (C 20 H 24 O 4 ) by an aldehyde dehydrogenase [27][28][29]. Crocetin then follows two parallel pathways:…”
Section: Introductionmentioning
confidence: 99%
“…Crocetin is glucosylated by glucosyltransferases to form crocins (crocetin glycosides), primarily crocin-4, by the addition of gentiobiose (GeOH: C 12 H 22 O 11 ), a disaccharide of two glucose units [27][28][29]. In summary: Crocetin + GeOH → Crocin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation